The Quality of Democracy in America: a Comparative Analysis, 1972-2021 - Ramírez Franco, Luz Dary; Sánchez Andrés, Antonio (Revista del CLAD Reforma y Democracia, 2023)
This article presents a descriptive and statistical analysis of two of the most prominent transnational indexes in conceptualizing and measuring democracy, Freedom House and the Polity Project, for the American countries. The data ratify the current debate on the persistence of democratic heterogeneity in terms of the degree and development of democracy, both at the level of the continent and its sub-regions. It is observed that most of the countries are included in democracies that do not reach the maximum values assigned by both measurements. The correlation analysis shows an inverse and significant relationship between them, which is novel, given that most studies find convergence. Finally, it is confirmed that GDPpc is not a variable that explains by itself the evolution and quality of democracy.